Cerebrovascular hemodynamics in Alzheimer's disease and vascular dementia: A meta-analysis of transcranial Doppler studies - Sabayan, Behnam; Jansen, Steffy; Oleksik, Anna M.; van Osch, Matthias J.P.; van Buchem, Mark A.; van Vliet, Peter; de Craen, Anton J.M.; Westendorp, Rudi G.J. (Ageing research reviews, 2012)
► Both ageing and dementia are associated with alteration in cerebral hemodynamics. ► We performed a meta-analysis on patterns of cerebral hemodynamics in demented patients compared to healthy elderly subject. ► Patients with Alzheimer's disease and vascular dementia had lower integrity in their arterial perfusion. ► Patients with Alzheimer's disease and vascular dementia had decreased cerebrovascular compliance. ► The magnitude of disturbances in cerebral hemodynamic is greater in vascular dementia compared to Alzheimer's disease. Alteration in cerebrovascular hemodynamics has reported in both ageing and dementia. However, it is still unclear whether this alteration follows similar pattern in ageing and in different dementia pathologies. The aim of this meta-analysis was to investigate changes in cerebral blood flow velocity and pulsatility index in two most common forms of dementia; Alzheimer's disease and vascular dementia, using transcranial Doppler studies. A literature search was conducted in Pubmed, EMBASE and Web of Science. After initial screening of 304 articles and removing duplicates, a total of 53 articles, published between 1980 and 2010, were reviewed. Finally 12 articles were included in the meta-analysis. For each study, effect sizes (ES) indicating the standardized mean differences of the hemodynamic measures between two groups were calculated. Using random effect models, pooled estimates of ES were measured. Patients with Alzheimer's disease (ES=−1.09, 95% CI −1.77 to −0.44, p=0.004) and vascular dementia (ES=−1.62, 95% CI −2.26 to −0.98, p<0.001) had significantly lower cerebral blood flow velocity compared with healthy aged-matched controls. In addition, pulsatility index was significantly higher in both Alzheimer's disease (ES=0.5, 95% CI 0.28–0.72, p<0.001) and vascular dementia patients (ES=2.34, 95% CI 1.39–3.29, p<0.001). Patients with Alzheimer's disease had lower pulsatility index (ES=−1.22, 95% CI −1.98 to −0.46, p=0.002) compared to subjects with vascular type of dementia. Patients with Alzheimer's disease and vascular dementia have a pronounced disturbance in their cerebrovascular hemodynamics. The severity of disturbances in cerebral hemodynamics is significantly lower in Alzheimer's disease compared to vascular dementia.